Effect of adding of powder and ethanolic extract of thymus vulgaris and rosemary on the body and internal organs weight of broiler (Journal of Hama University, 2022)
This study was carried to investigate the effect of adding of thymus and rosemary powder to broiler standard diet, and alcoholic extract of both planets on some productive performance. 188 one-day old Ross strain unsexed chicks were randomly distributed into seen groups (26 chicks for each), as flowing: First group is control without any addition, second and third groups included the addition of 1 g thymus powder/kg diet and 1 g rosemary powder/kg diet respectively, and the fourth group included the addition of mixture of one-gram thymus and one-gram rosemary powder/kg diet. Fifth and sixth groups, the addition of 1 ml thymus alcoholic extract /L drinking water and 1 ml rosemary alcoholic extract /L drinking water respectively, and the seventh group included the addition of mixture of one ml thymus alcoholic extract and one ml rosemary alcoholic extract /L drinking water. The results showed significantly (P0.05) of adding the studied plant powder on the average weight of the heart muscle, lungs, and the legs. The two plants had a significant effect (p